Stress contours in the connecting-rod under the dynamic load and the oil film’s pressure of the connecting-rod big end - Hai, Tran Thi Thanh (Vietnam Journal of Science and Technology, 2020)
Under load apply to the connecting-rod and the pressure in the lubricant oil film change the stress in the connecting-rod during the operating cycle. This problem is the one of the characteristics we need to consider when studying the connecting-rod big end bearing. A specific experimental device and the connecting-rod model of photoelastic material are used to determine the load diagram, measure the oil film pressure, and visualize the state of stress. The connecting-rod is subjected to simulation load as in the engine. The lubricated oil film pressure is measured by the pressure sensor and also calculated by numerical modelization method with the same load diagram. The method chosen to visualize the stress state in the dynamically loaded connecting rod is the transmission photoelasticimetry. This method allows the visualization of the isochrones fringes, which are lines of equal difference regarding main stresses in the connecting-rod. The stress contour’s images of the connecting-rod at different angles of the crankshaft are realized by a CCD camera. The measured stress contours are compared to the calculated stress contours by the Algor software. The results show globally a correspondence between the experimental isochrones fields and the calculated isochrones fields.